Primary malignant tumors of the trachea: a retrospective analysis of the clinical data of 79 patients treated in a single center - Chen, Qiuyan; Xue, Keying; Wu, Yigen; Luo, Bingqing; Lin, Yuyi (Frontiers in Oncology, 2025)
BackgroundPrimary malignant tumors of the trachea are rare. There are few data on such tumors, the understanding of the disease is limited, and the best treatment plan has not yet been determined.MethodsClinical data obtained from the medical records of 79 patients with primary malignant tumors of the trachea treated in our hospital between August 2008 and August 2023 were retrospectively analyzed. The clinical data included demographic characteristics (age, sex), carcinogen exposure (smoking or drinking), symptoms, histology, primary tumor location (cervical trachea, intrathoracic trachea or bronchus), primary tumor range, lymph node status, and treatment. SPSS 26.0 software was used for statistical analysis. The Kaplan– Meier method was used to calculate the survival rate, and the log-rank test was used to compare the survival differences between groups. Multivariate analysis was performed using the Cox regression model.ResultsPatients with primary tracheal ACC were significantly younger than those with SCC were (45.5 years old vs. 66.0 years old, P = 0.000007). SCC is more common in smoking and male patients, whereas ACC and other pathological types are more common in nonsmoking and female patients. ACC patients were less likely to have lymph node metastasis than SCC patients were (12.5% vs. 36%, P = 0.047). The 3-year, 5-year and 10year overall survival rates were 69.9%,62.3% and 34.2%, respectively, and the median OS was 96 months. The 3-year overall survival rates of patients with ACC, SCC, and other pathological types were 86.3%, 47.1%, and 71.4%, respectively. The 5-year overall survival rates were 77.0%, 26.5% and 62.5%, respectively. The 10-year overall survival rates were 39.5%, 13.3% and 62.5%, respectively. The overall survival of SCC patients was the shortest among all pathological types, and the difference was statistically significant. The COX regression analysis further demonstrated that a higher N stage is significantly associated with an elevated risk of distant metastasis.ConclusionPrimary malignant tumors of the trachea are rare, and the best treatment has not yet been determined. Although most patients in this center are treated via a variety of methods, whether this varied approach to treatment is the reason for the higher overall survival cannot be ascertained. Moreover, most patients in our center received a variety of treatments, so a survival analysis of specific treatment modalities was not possible. Thus, more studies involving more patients are needed to ascertain the optimal treatment plan for malignant tracheal tumors.